I7-Gestor: uma ferramenta de automação comercial para pequenos comércios no município de Itacoatiara - Amazonas - Silvério, Anderson Nogueira (Brasil, 2022)
The technologies present in the daily life of modern society have changed completely the way to communicate, request services and even study. In that In this context, process automation is present, in which repetitive tasks can be made by computerized equipment. The objective of this study is to develop a commercial automation tool to serve small businesses in the city of Itacoatiara-Amazonas. The methodology adopted to carry out this research was action research together and a qualitative approach, through observation of the routine of a local commerce and obtaining a commercial automation software for study. With the results obtained in the research, it was possible to develop a software commercial automation that satisfactorily meets the commerce of the city of Itacoatiara-Amazonas.